CORREPTIO FRATERNA SEBAGAI SARANA MENGEMBANGKAN KOMUNITAS RELIGIUS - Andreas Maurenis Putra (Jurnal Orientasi Baru, 2016)
Correptio fraterna has been an effort which will never be end in living a religious life. In the diversity of members of the religious community, Correption fraterna need to be a pillar to sustain the goal of a community life in accordance with the Augustines ideal for religious life that has been written in his Regula. Live harmoniously in one mind and heart intent upon God is the main point of St. Augustines ideal of religious life. Correptio fraterna occupies an important position in the community life as confirmed by St. Augustine himself and strengthened by several viewpoints such as biblical, theological and spiritual. With a background of reality which could be found in every religious community community life and all its efforts to give value to Correptio fraterna, expectedly Correptio fraterna has to be the strong foundation to foster the life of a religious community despite having many challenges to be faced. On the one hand Correptio fraterna should collide with the challenges of the community life such as the gap between senior-junior, different interpretation and the reluctancce to correct that led to omission. On the other hand, Correptio fraterna must be the foundation to support the community life and finding the true meaning of Correptio fraterna for the sake of a religious community metanoia towards the ideals of living in harmony, one heart and mind intent upon God.